Perubahan Tahapan Dan Bentuk Rumah Tradisional Masyarakat Adat Suku Sentani Dipesisir Danau Sentani Di Kabupaten Jayapura - Deasy Widyastomo (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
Traditional houses scattered with various unique forms in the territory of Indonesia reveal a distinctive and unique local cultural identity in their states and display the richness of the traditional culture of the Indonesian nation. The diversity of traditional houses in this archipelago has a high artistic feel in architectural forms, motifs, and similarities in philosophy. Still, it is rich in architectural structures that differ from one place to another. The traditional housing group for the Sentani tribe in Ifale village is formed from the unity of three different kinship groups of indigenous peoples. The three kinships live one life together as the traditional Sentani people and still maintain the ancestral traditions passed down from generation to generation by adjusting to current life developments. The traditional house of the Sentani indigenous people has changed with the entry of knowledge and changes in people's lifestyles. The shift in housing does not affect the existence of their traditional residence, a nation's wealth that must be maintained and protected. This study aimed to study changes in building traditional Sentani houses on Lake Sentani in Jayapura Regency. The research method used in this research is descriptive in conducting data analysis using qualitative methods (field data) and quantitative (excel program and SPSS). The study results show that changes in the way of building the traditional houses of the indigenous people of the Senani tribe towards the process of building and using house construction for the period 1907-1925 and 2021 have changed from places formed by their ancestors to modern traditional houses. These changes are influenced by the increase in community economic growth, public awareness of environmental and human health, and construction use following the latest developments in construction technology.